Implementation of Islamic Education Philosophy in Elementary School Learning - Desiana Widya Ningrum (Jurnal Pendidikan Nusantara, 2024)
This article discusses the implementation of Islamic educational philosophy in elementary school learning. This study uses a qualitative research method, namely a process that uses sentences or words to conduct research and write it. The type of library research aims to explore data and information from various sources, such as books, journals, papers, documents, notes, and others. The results show that implementing Islamic educational philosophy in elementary school learning is very important even though there are challenges that will be faced if the solution is correct. If there is support from various parties, it will undoubtedly be successful. It will be able to form a young generation who have a strong Muslim character to face challenges in the current era of globalization and can form a young generation who are intelligent and have noble character.